Effectiveness of bronchial thermoplasty in severe asthma in 'real life' patients compared with those recruited to clinical trials in the same centre. (December 2015) - Bicknell, Stephen; Chaudhuri, Rekha; Lee, Nicola; Shepherd, Malcolm; Spears, Mark; Pitman, Nick; Cameron, Euan; Cowan, Douglas; Nixon, Julie; Thompson, Joyce; McSharry, Charles; Thomson, Neil C.
Published information on the effectiveness of bronchial thermoplasty (BT) for severe asthma in 'real life' patients is limited. We compared safety and efficacy outcomes 12 months post procedure in 10 clinic patients and 15 patients recruited to clinical trials of BT at the same centre. Baseline asthma severity was greater in the clinic group. Adverse events were similar. Clinical improvements occurred in 50% of the clinic patients compared with 73% of the research patients.